Neonatal Seizures and Neurodevelopmental Outcome - Waheed, MA (Bangladesh Journal of Medicine, 2023)
Background: Neonatal period is the most vulnerable time for the occurrence of seizures. There are various etiological factors of neonatal seizures and increasing evidence suggests that neonatal seizures are associated with adverse neurodevelopment outcomes. The aim of the study is to determine of causes of neonatal seizures with outcome during management and long-term post-natal outcome. Methods: This prospective study conducted in Rangpur Mother and Children Hospital from 1st July to 2017 to 30th June 2022. Term newborn babies admitted in NICU with convulsion were the samples. A prepared and pretested “Protocol” containing Part-A and Part-B was used - Part-A in neonatal intensive care unit and Part-B in the attached Disability Research Center. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 200-201